Integrating STEAM into flip flop model to improve students’ understanding on composition of functions during online learning - Naufal Ishartono; Rafiza binti Abdul Razak; Muhammad Noor Kholid; Janu Arlinwibowo; Asyifa Nur Afiyah (Jurnal Infinity, 2024)
Some previous studies tried to improve students' understanding of the concept of the composition of functions. However, only some research results still examine efforts to increase student understanding of the concept taught online, especially by utilizing the STEAM-integrated Flip Flop learning model. Therefore, the purpose of this study is to analyze the level of effectiveness of the application of the STEAM-integrated Flip Flop model in increasing students' understanding of composition function material taught online. To answer the purpose of the study, the authors compared the model with the Flipped Learning model and the conventional learning model. The quantitative method with a pretest-posttest control group design model is employed in the present study by engaging 90 Indonesian senior high school students. This study finds that the STEAM-integrated Flip Flop model is significantly better at improving students' understanding of the composition of function concepts than conventional models. However, the same result is not found if compared with the Flipped Learning model. Though the average score of the STEAM-integrated Flip Flop model is better than the Flipped Learning model, the difference is not significant. This study also describes the related syntax of the STEAM-integrated Flip Flop model that high school math teachers can use to teach better composition functions online.